A Study of Customer Loyalty towards Yoga Marketing Relationship in the Indian Urban Market - Kawari, Neha (Ushus Journal of Business Management, 2021)
This paper examines the popular culture of Yoga and aims to shed light on the theoretical understanding of relationship marketing and its main components that have a direct or indirect impact on any relational approach. Marketing through spirituality has become a significant topic of discussion as it affects the consumption behaviour of people. Therefore, spiritual organisations are launching and selling their own products for the customers to capture the market. Here, in this study, Yoga and „Pranayam‟ are considered dimensions of spirituality. It is observed that people rely on a spiritual guru for performing Yoga and Pranayam. This research was done for the city of Hubballi with 150 respondents from Yoga organisations, studios as well as people practising it. Results show that flexibility and removing stress were the major benefits from Yoga marketing.